Protective effects of L‐arginine on the intestinal epithelial barrier under heat stress conditions in rats and IEC‐6 cell line. Issue 1 (11th November 2019) - Huang, Liqing; Yin, Peng; Liu, Fenghua; Liu, Yilin; Liu, Yanhan; Xia, Zhaofei
Abstract: Heat stress (HS) and the associated restricted blood flow to the intestine have been proven to destroy intestinal integrity. Considering the beneficial properties of L‐arginine on gut function, we investigated the protective effects of L‐arginine on the intestine under HS conditions. In vivo, the serum cortisol level and the rectal temperature increased in response to HS. Under HS, the intestinal damage showed obvious morphological changes. Furthermore, HS decreased the mRNA and protein expression levels of Nurr1, ZO‐1, occludin, claudin‐6 and E‐cadherin, increased the mRNA expression of NF‐κB and IL‐1β, and increased the protein expression of cleaved caspase‐3. In contrast, L‐arginine supplementation maintained intestinal integrity and increased the villus/crypt ratio. L‐arginine also suppressed the expression of inflammation‐related genes and the protein expression of cleaved caspase‐3, whereas it upregulated the mRNA and protein expression of tight junction proteins and LC3B protein expression. In vitro, L‐arginine attenuated HS‐induced apoptosis as demonstrated by flow cytometry and decreased cleaved caspase‐3 protein expression. L‐arginine induced autophagy, which was demonstrated by decreased expression of p62 and p‐mTOR/mTOR, and increased expression of LC3B. The protein expression levels of TJ proteins also enhanced by L‐arginine in IEC‐6 cells. Taken together, these results suggest that L‐arginine can alleviate intestinal damage and protect the intestinal integrity by suppressing local inflammation response, promoting the production of TJs and facilitating autophagy under HS conditions.